The Effectiveness of Teaching Metacognitive Strategies on Psychological Empowerment and Work-Family Conflict of Female Educators Working in Specific Disease Centers - abbasi amiri, zohreh; bazzazian, saeideh (Iranian Journal of Neurodevelopmental Disorders, 2023)
Background and Purpose: Conflicts are an unavoidable part of life and occur in different dimensions, such as family, work, and interpersonal relationships, and need to be solved. The aim of this study was to determine the effectiveness of metacognitive strategies training on work-family conflict and psychological improvement of female trainers in specific learning disorders centers. Method: The research is quasi-experimental with a pretest-posttest design with a control group. The statistical population included all female educators working in special learning disability centers in Tehran in 2021-22, from which 60 people were selected using the available sampling method and randomly divided into two experimental and control groups (each group includes 30 people). The instruments used included the Carlson et al. (2000) questionnaire and the Spritzer (1995) Psychological Competence Questionnaire completed by the experimental and control groups in pre-test and post-test. The experimental group took part in metacognitive strategies training for 8 sessions. Data was analyzed using SPSS26 software and Two-way mixed analysis of variance (MANCOVA). Results: The results indicate the significant effect of teaching metacognitive strategies on work-family conflict and psychological empowerment of female educators working in special learning disability centers (P≥0.05). Conclusion: Metacognitive strategies training, as a practical skill, is recommend for female trainers working in specific learning disorder centers